Leukotrienes in Atherosclerosis: New Target Insights and Future Therapy Perspectives - Graziano Riccioni; Alessandra Zanasi; Nicola Vitulano; Barbara Mancini; Nicolantonio D'Orazio (Mediators of Inflammation)
Atherosclerosis represents an important chronic inflammatory process associated with several pathophysiological reactions in the vascular wall. The arachidonic acid, released by phospholipase A2, is an important substrate for the production of a group of lipid mediators known as leukotrienes, which induce proinflammatory signaling through the activation of specific BLT and CysLT receptors. The interaction of these substances in the vascular wall determines important morphological alterations like the early lipid retention and the accumulation of foam cells, the development of intimal hyperplasia, and advanced atherosclerotic lesions, and it plays an important role in the rupture of atherosclerotic plaque. Many studies regarding myocardial ischemia and reperfusion show that leukotriene signaling may be involved in the development of ischemic injury. For these, reasons both leukotriene synthesis inhibitors and leukotriene receptor antagonists have been suggested for inducing beneficial effects at different stages of the atherosclerosis process and may represent a new therapeutic target in the treatment of atherosclerotic vessel diseases, in particular in acute coronary syndrome.